2014
DOI: 10.1007/s13277-013-1594-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms of ESR1, ESR2, CYP17A1, and CYP19A1 and the risk of breast cancer: a case control study from North India

Abstract: Estrogen is a key driver of breast cancer and genes involved in its signaling and biosynthesis are crucial in breast cancer progression. In this study, we investigated the role of estrogen signaling and synthesis related genes polymorphism in susceptibility to breast cancer risk in North India population in a case-control approach. We examined the association of single nucleotide polymorphism (SNP) in estrogen receptors, ESR1 (rs2234693) and ESR2 (rs2987983); estrogen biosynthesis enzymes, CYP17A1 (rs743572); … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 44 publications
2
25
1
Order By: Relevance
“…In a stratified analysis by menopausal status, the association between the rs10046 C allele and BC was more evident in premenopausal women than postmenopausal women. Chattopadhyay et al (2014) previously observed that rs700519 had a significant association with BC risk in North Indian women, which was strongly affected by menopausal status. Sun et al (2015) also reported that rs700519 is associated with susceptibility to BC among the Han Chinese population.…”
Section: Discussionmentioning
confidence: 92%
“…In a stratified analysis by menopausal status, the association between the rs10046 C allele and BC was more evident in premenopausal women than postmenopausal women. Chattopadhyay et al (2014) previously observed that rs700519 had a significant association with BC risk in North Indian women, which was strongly affected by menopausal status. Sun et al (2015) also reported that rs700519 is associated with susceptibility to BC among the Han Chinese population.…”
Section: Discussionmentioning
confidence: 92%
“…Most recently, Chattopadhyay et al [71] reported significant associations between SNPs in ERα (rs2234693), ERβ (rs2987983), CYP17A1 (rs743572) and CYP19A1 (rs700519) and breast cancer risk in a case control study performed in North India. The study included 360 cases with corresponding controls matched on age, sex, ethnicity, and geographical location.…”
Section: Role Of Genetic Variation In Estrogen Metabolismmentioning
confidence: 99%
“…Many studies have evaluated the association between SNPs in estrogen-related genes, such as CYP17 , CYP19 , CYP1A1 , CYP1B1 , COMT , GSTP1 , and ER α/β, and the risk of breast cancer, especially in postmenopausal women [14,15,16,17,18,19,20,21]. Polymorphisms in these genes have been reported to affect the regulation, transcription, and activity of the enzymes, as well as subsequent exposure to endogenous estrogen and the development of breast cancer [14].…”
Section: Introductionmentioning
confidence: 99%